Process evaluation of a pragmatic implementation trial to support self-management for the prevention and management of type 2 diabetes in Uganda, South Africa and Sweden in the SMART2D project. Issue 5 (26th September 2022) - van Olmen, Josefien; Absetz, Pilvikki; Mayega, Roy William; Timm, Linda; Delobelle, Peter; Alvesson, Helle Mölsted; Naggayi, Glorai; Kasujja, Francis; Hassen, Mariam; de Man, Jeroen; Sidney Annerstedt, Kristi; Puoane, Thandi; et al.
Abstract : Introduction: Type 2 diabetes (T2D) and its complications are increasing rapidly. Support for healthy lifestyle and self-management is paramount, but not adequately implemented in health systems. Process evaluations facilitate understanding why and how interventions work through analyzing the interaction between intervention theory, implementation and context. The Self-Management and Reciprocal Learning for Type 2 Diabetes project implemented and evaluated community-based interventions (peer support program; care companion; and link between facility care and community support) for persons at high risk of or having T2D in a rural community in Uganda, an urban township in South Africa, and socioeconomically disadvantaged urban communities in Sweden. Research design and methods: This paper reports implementation process outcomes across the three sites, guided by the Medical Research Council framework for complex intervention process evaluations. Data were collected through observations of peer support group meetings using a structured guide, and semistructured interviews with project managers, implementers, and participants. Results: The countries aligned implementation in accordance with the feasibility and relevance in the local context. In Uganda and Sweden, the implementation focused on peer support; in South Africa, it focused on the care companion part. The community–facility link received the least attention. Continuous capacity building received a lot of attention, but intervention reach, dose delivered, and fidelity varied substantially. Intervention-related and context-related barriers affected participation. Conclusions: Identification of the key uncertainties and conditions facilitates focus and efficient use of resources in process evaluations, and context relevant findings. The use of an overarching framework allows to collect cross-contextual evidence and flexibility in evaluation design to adapt to the complex nature of the intervention. When designing interventions, it is crucial to consider aspects of the implementing organization or structure, its absorptive capacity, and to thoroughly assess and discuss implementation feasibility, capacity and organizational context with the implementation team and recipients. These recommendations are important for implementation and scale-up of complex interventions. Trial registration number: ISRCTN11913581 .